Exploring The Factors That Enhance Learning And Self-Efficacy Of Midwifery Students: A Sem-Pls Analysis - adriana egam (Universitas Nahdlatul Ulama Surabaya, 2023)
This study aims to identify the influencing factors on midwifery students' learning and self-efficacy development in Indonesia. The study employed a descriptive and cross-sectional analysis using an online questionnaire that included demographic data and analysis factors such as environmental learning, lecturer quality, learning methods, self-motivation, social support skills, assessment and feedback, circumstances of learning enhancement, and perceived self-efficacy. The study population was students majoring in midwifery at the Ministry of Health Health Polytechnic Sorong, who are currently enrolled in diploma and undergraduate programs. A total of 40 respondents completed the survey. The results showed that learning methods have a significant influence on both learning improvement and self-efficacy. The study highlights the need to identify and evaluate the various factors that influence midwifery students' learning to develop more effective and efficient strategies and methods to increase the quality and effectiveness of midwifery education. The findings of the study could have implications for the future of education and health in Indonesia.